1999
DOI: 10.1159/000020914
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fetal Echogenic Bowel in the Second Trimester

Abstract: Previous studies cite different possible etiologies for fetal echogenic bowel (FEB). The purpose of this study was to evaluate the possible etiologies for second-trimester FEB, and to provide clinical guidelines for evaluation of this finding. The study included 79 patients diagnosed with FEB in the second trimester. Fifteen cases (19%) were associated with maternal vaginal bleeding. Of these, 12 patients underwent amniocentesis, 9 of which had visible blood products in the amniotic fluid. Seven cases (8.9%) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 12 publications
5
44
0
1
Order By: Relevance
“…Therefore, when considering differential diagnosis for fetal echogenic bowel it is necessary to scan for other markers of aneuploidy, assessment of growth, screen for infections and assess the risk status for cystic fibrosis as well as structural malformations, especially gastrointestinal [1,7,8]. Moreover, Yuval et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when considering differential diagnosis for fetal echogenic bowel it is necessary to scan for other markers of aneuploidy, assessment of growth, screen for infections and assess the risk status for cystic fibrosis as well as structural malformations, especially gastrointestinal [1,7,8]. Moreover, Yuval et.…”
Section: Discussionmentioning
confidence: 99%
“…al. [8] least one possible explanation is the access of blood or blood products to the amniotic fluid. The echogenicity in these cases is most likely secondary to ingested blood in the fetal gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Different pathological conditions such as trisomy 21, cystic fibrosis, severe early onset of IUGR, thalassemia, intramniotic bleeding, gastrointestinal obstruction, mesenteric ischemic, perinatal death and cytomegalovirus infections have been associated with second trimester hyperchoid bowel. [25][26][27] Poor perinatal outcome has been noted in 1/3 of pregnancies with FEB including chromosomal defect in 9% of the cases, cystic fibrosis in 2%, congenital infection in 3% and IUGR in 8%.…”
Section: Fetal Echogenic Bowelmentioning
confidence: 99%
“…DNA analysis is used to screen for CF mutations. The mutation panel is currently expanded in many coun-tries and includes up to 32 mutations in certain centers [1,3]. A normal test does not completely exclude CF, as rare or unknown mutations may be present, thus making a postnatal sweat test necessary [9,11].…”
Section: Commentmentioning
confidence: 99%
“…Denholm et al [2] first reported a relation to cystic fibrosis (CF) in 1984. Once considered a normal variant, FEB has since been linked to many diseases including CF, aneuploidy, congenital infection, fetal abnormalities, gastrointestinal obstruction or perforation, intra-amniotic bleeding, in utero growth retardation (IUGR), intrauterine fetal death (IUFD) and fetal alcohol syndrome [3][4][5][6]. The purpose of this study was to analyze diagnostic findings in FEB and the corresponding outcome of pregnancy in order to identify indicators of high-risk situations.…”
Section: Introductionmentioning
confidence: 99%